2017
DOI: 10.1063/1.4983851
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of radio frequency ring-shaped magnetized discharge sputtering plasma using two facing ZnO/Al2O3 cylindrical targets for Al-doped ZnO thin film preparation

Abstract: Spatial structure of high-density radio frequency ring-shaped magnetized discharge plasma sputtering with two facing ZnO/Al2O3 cylindrical targets mounted in ring-shaped hollow cathode has been measured and Al-doped ZnO (AZO) thin film is deposited without substrate heating. The plasma density has a peak at ring-shaped hollow trench near the cathode. The radial profile becomes uniform with increasing the distance from the target cathode. A low ion current flowing to the substrate of 0.19 mA/cm2 is attained. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…36,37) It is found that the radial profile for z = 10 mm has a peak of approximately 0.1 mA at r = 45 mm positioned at the center of the hollow groove. The plasma density n i for I is = 0.1 mA is estimated to be 7 × 10 10 cm −3 with the assumption of an electron temperature of T e = 46400 K 30) based on…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…36,37) It is found that the radial profile for z = 10 mm has a peak of approximately 0.1 mA at r = 45 mm positioned at the center of the hollow groove. The plasma density n i for I is = 0.1 mA is estimated to be 7 × 10 10 cm −3 with the assumption of an electron temperature of T e = 46400 K 30) based on…”
Section: Resultsmentioning
confidence: 99%
“…The retentivity and the coercive force of the neodymium material are 12700 G and −11500 Oe, respectively. Figure 3 30) shows the 2D magnetic flux lines around the hollow groove. It is found that the magnetic field lines close the outlet of the groove so that electrons are confined in the hollow trench.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that hollow-cathode sputtering can be utilized to deposit AZO films for solar cell applications. Sumiyama et al 42 used radiofrequency (RF) ring-shaped magnetized discharge plasma sputtering to deposit AZO thin films and reported that this technique could produce AZO films with high transmittance. Although these sputtering systems produced good results, in these systems, metallic targets with specific dimensions and compositions are required to deposit any material.…”
Section: Introductionmentioning
confidence: 99%